The effectiveness of task-based instruction on third-year secondary students’ English speaking performance - BADR, HAYTHAM MORSHED ELSAYED ABDALLA (2022)
This study intended to investigate the impact of task-based instruction (TBI) as a communicative teaching strategy on secondary students’ oral production of more fluent, lexically sophisticated, lexically diverse and syntactically complex language as well as exploring teachers’ perceptions and opinions towards the possibility of effective and successful use of this strategy to improve secondary students’ speaking abilities in the Egyptian classroom context. The underlying hypothesis was the ability of TBI to bring about the necessary outcome in terms of fluency, lexical sophistication, lexical diversity and syntactic complexity as a result of the communicative environment created and the mental process enhanced by TBI. The mixed-methods research approach was embraced to glean the research data from two different samples using two main research tools: pre-post tests to collect the quantitative data and semi-structured interviews to gather the qualitative data. Five other research tools were utilized in the current research including an Oxford quick placement test to ensure the homogeneity of the research sample in terms of language proficiency level prior to the experiment and four automatic computer-based tools (Praat, TAALES, TAALED and L2SCA) to accurately and objectively score and assess students’ oral performance on four fluency measures, three lexical sophistication measures, three lexical diversity measures and four syntactic complexity measures. The quantitative data was deductively collected from ninety two second language students equally and randomly divided into two intact groups, while the qualitative data was inductively gleaned from eight language teachers. The results from the quantitative data exhibited the positive impact of TBI on students’ speaking performance for some of the measures examined, despite the short treatment period which lasted for eleven weeks. Moreover, the results from the qualitative data revealed the conflicting beliefs of teachers towards TBI; namely, the ability of TBI to improve secondary students’ speaking skills but with some challenges against its implementation in the Egyptian classroom settings. Based on these results, some pedagogical implications were provided to be considered by language teachers, syllabus designers, administrative officials and researchers in the second language acquisition (SLA) domain and some other recommendations for future potential readers and researchers were made.